2007
DOI: 10.1109/tac.2007.910653
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Supervisory Control Based on Discrete Event Systems With Flexible Marking

Abstract: This paper proposes a two-level hierarchical supervisory control scheme for a discrete event system (DES), where the low-level is represented in the standard Ramadge-Wonham framework and the high level is represented by a DES with flexible marking (DESFM). As shown, the flexibility in the definition of marking provided by a DESFM simplifies the modeling of the high-level marking behavior. This approach, when compared with other approaches, requires less events and states to model the highlevel, while guarantee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 23 publications
0
14
0
3
Order By: Relevance
“…6. Also consider that, in some hierarchical control approach one is concerned with the input-output behaviour of the workcell for coordination purposes with other workcells (Cunha and Cury, 2007;Schmidt and Breindl, 2011). Thus, the relevant events are the input event for the workcell x and the two output events a 1 and a 2 , therefore Σ r = {x, a 1 , a 2 , τ}.…”
Section: Case Studymentioning
confidence: 99%
See 3 more Smart Citations
“…6. Also consider that, in some hierarchical control approach one is concerned with the input-output behaviour of the workcell for coordination purposes with other workcells (Cunha and Cury, 2007;Schmidt and Breindl, 2011). Thus, the relevant events are the input event for the workcell x and the two output events a 1 and a 2 , therefore Σ r = {x, a 1 , a 2 , τ}.…”
Section: Case Studymentioning
confidence: 99%
“…7. One of the most important conditions for hierarchical control approaches like (Cunha and Cury, 2007), , or (Schmidt and Breindl, 2011) is that θ(M ) has to be an OP-abstraction. From definition 1, it can be shown that θ(M ) is not an OP-abstraction by making s = xyzwv 1 rzwv 2 ∈ N and t = a 1 ∈ Σ * r such that θ(s)t = xa 1 ∈ L m (θ(M )), but there is no t ∈ Σ * such that st ∈ L m (M ) and θ(st ) = xa 1 .…”
Section: Case Studymentioning
confidence: 99%
See 2 more Smart Citations
“…No controle hierárquico, abstrações são usadas como modelos para o nível gerencial (alto-nível), permitindo a síntese de leis de controle que satisfaçam especificações deste nível da estrutura hierár-quica de controle (Wong e Wonham, 1996), (Torrico e Cury, 2004), (Schmidt et al, 2004), (Leduc et al, 2005), (Cunha e Cury, 2007), (Schmidt et al, 2007), (Hill, Cury, de Queiroz e Tilbury, 2008). Nesse caso, o modelo de alto-nível esconde eventos que correspondem a detalhes operacionais do comportamento do sistema, não-relevantes no mundo gerencial.…”
unclassified